Transformasi Peran Pendidik PPKn di Era Society 5.0 Menuju Pendidikan Humanis dan Digital - Fajriyah, Adelia Rachmawati; Ardinary, Cintya; Kasta, Malika Alia; Alwan, M. Hanif; Nurahma, Rihan Siti (CV. Kurnia Grup, 2025)
The Society 5.0 era presents new challenges for the world of education, including Pancasila and Citizenship Education (PPKn). The role of PPKn educators is required not only as a conveyor of knowledge, but also as a facilitator, innovator, and reinforcer of humanistic values amidst digital developments. This article aims to describe the transformation of the role of PPKn educators in the Society 5.0 era, identify the challenges faced, and formulate innovative strategies in integrating humanistic values with the use of digital technology. The research method used is a literature study by reviewing books, journal articles, and official documents. The results of the study indicate that PPKn teachers need to master digital literacy, implement technology-based learning models, and continue to emphasize the formation of civic character. This transformation is key to realizing education that is relevant, adaptive, and oriented towards strengthening national identity in the digital era.